COVID-19, mortality, and nursing homes: A literature and data review and policy discussion - Mark J. Warshawsky (American Enterprise Institute (AEI), 2022)
It is well established from research studies and basic data analysis that there is an exponential relationship between age and the infection to fatality ratio for COVID-19. Hence, the high mortality of the pandemic has been concentrated among the elderly. The close living arrangements of nursing homes exacerbated that tendency, and mortality from COVID was initially very high there. The vector of infection often came from staff. In the absence of vaccines and effective medical treatment and natural immunity, various non-pharmaceutical interventions were imposed by governments on general society and nursing homes. The evidence on their effectiveness is modest and mixed, although they seemed to have had at least temporary reducing effects. But the price of these socially isolating interventions was high on other causes of death, including in nursing homes. Hence, with the availability of effective vaccines, and more recently boosters, it was essential to the reduction of national mortality that quick and complete treatment focus be on the elderly, nursing home residents, and their caregivers. Although there has been substantial progress here, especially seen with reduced mortality at nursing homes, spikes still occur, and vaccine hesitancy gaps remain. So more needs to be done, especially for boosters and especially for staff, as the US now discusses and implements the return to normalcy. A targeted mix of mandates and incentives and culturally aware effective outreach are appropriate for these groups.
Keywords: A; 330; Aging; COVID-19; Health Care Policy; Health Care Policy Responses On COVID-19; Vaccines